Measuring Medical Residents' Well-Being - Scott Cottrell; Mary Warden; Cynthia Graves; Mahreen Hashmi; Linda Nield; Hollynn Larrabee; Nathan Lerfald; Heather Clawges; Norman Ferrari (MedEdPORTAL, 2013)
Abstract Introduction Research suggests that well-being impacts residents' ability to learn and provide patient care. The purpose of this study was to investigate the descriptive statistics, factors and the internal reliability of the Resident Well-being (RWB) scale. Analyses were also conducted to investigate the construct validity of the responses to the RWB. Methods The resource includes an investigation of the descriptive statistics, factors and the internal reliability of residents' responses to the RWB scale. This resource also includes an investigation of the construct validity of the RWB by exploring potential relationships between residents' well-being and two theoretically related constructs: the quantity of sleep and rotation demands. The development of the RWB and an investigation of the internal reliability and validity of the responses help contribute to how educators can assess residents' well-being and inform residency program implementation. This project also serves as the beginning of a long-term project to efficiently measure the well-being of residents and other learners in the health care professions. Results The RWB responses were internally reliable (Cronbach's alpha = .89) and one factor (i.e., well-being) was distinguished. There was a statistically significant relationship between the frequency residents slept and well-being. There was also a statistically significant effect of rotations' time intensiveness on residents' well-being; however, effect sizes suggest the amount of sleep and rotation intensiveness explains only a small to a moderate amount of variance of resident well-being. Discussion The RWB is a tool that program directors may utilize to monitor residents' well-being. Future research is required to investigate how other triggers, such as program quality and life-stressors, may impact residents' well-being. Future research may also investigate how the RWB may be applied to other health professionals, as learners across the disciplines struggle to negotiate a balance between their personal lives, learning, and patient care.